Combined Expression of Genetic Adjuvants Via mRNA Electroporation Exerts Multiple Immunostimulatory Effects on Antitumor T Cells. Issue 2 (February 2019) - Weinstein-Marom, Hadas; Levin, Noam; Pato, Aviad; Shmuel, Nofar; Sharabi-Nov, Adi; Peretz, Tamar; Eisenberg, Galit; Lotem, Michal; Itzhaki, Orit; Besser, Michal J.; Gross, Gideon
Abstract : Adoptive transfer of tumor-infiltrating lymphocytes (TILs) or gene-modified T cells expressing antitumor TCRs or chimeric antigen receptors often yields a high rate of clinical response in several types of cancer. New approaches for enhancing the functional properties of antitumor T cells could improve the clinical outcome of these treatments. To this end, we created 3 classes of genes, each designed to operate autonomously upon expression in T cells. We recently reported on the enhancing effects of constitutively active toll-like receptor 4 (caTLR4), membrane (mem) interleukin-2, memIL-12, and memIL-15, and self-oligomerizing, constitutively active CD40 (caCD40). Here, we evaluated their combined effects on peripheral blood CD8 T cells and different antimelanoma TIL cultures following mRNA electroporation. Expression in CD8 T cells induced transient production of interferon-γ and prolonged and robust upregulation of CD25, CD69, 4-1BB, and OX40. The adjuvants enhanced cytolytic activity of TILs and production of interferon-γ and TNF-α in the presence of autologous, but not mismatched, melanoma for at least 3 days after electroporation. Expression of the 3 adjuvants in young TILs from different patients markedly increased the expression of CD25, OX40, 4-1BB, CD127, and CD28 and exhibited cooperative and, at times, synergistic effects. Furthermore, predefined mixtures of mRNA encoding these adjuvants markedly enhanced the specific antitumor response of selected TILs and killing of autologous melanoma cells by young TILs. Our findings suggest that combinations of these new genetic adjuvants can substantially improve the functional properties of antitumor T cells, offering a new tool of unique versatility in adoptive cell therapy.